Respuesta :

Answer: [tex]\frac{- 1}{11}[/tex]

Step-by-step explanation:

Note: the "." symbol stands for multiplication

Given,

[tex]\frac{2x+4}{3} \\[/tex]  - [tex]\frac{5x-7}{2}[/tex] = 5

First we the LCM = 6,

[tex]\frac{2(2x+4)}{2.3}[/tex] - [tex]\frac{3(5x-7)}{3.2}[/tex]= 5

Then, we join both sides, since they have same denominator

[tex]\frac{2(2x+4) - 3(5x-7)}{6}[/tex] = 5

Multiply again

[tex]\frac{4x+8 - 15x+21}{6}[/tex] = 5

Add the same numbers

[tex]\frac{-11x + 29}{6}[/tex] = 5

Transpose 6 to the other side

-11x + 29 = 5.6

-11x + 29 = 30

Transpose 29 to the other side

-11x = 30 -29

-11x = 1

Transpose 11 to the other side to get answer

x = [tex]\frac{-1}{11}[/tex]

Hope it helps! If you have any doubts, feel free to ask